Gestational Diabetes Causes, Diagnosis and Treatment - Sobrevia, Luis (IntechOpen, 2013)
This book summarizes several aspects of GD, which is caused by not well-understood multifactorial mechanisms. Common strategies seem to be key in the understanding of the syndrome, i.e., endothelial dysfunction and the role of other placenta cells such as trophoblasts. It is a book that will definitively help to increase the knowledge-based management of GD for the well being of the mother and the fetus. Several chapters lead us to the conclusion that pre-pregnancy and antenatal screening of women is required, something that will improve the management and outcome of a current pregnancy but will also optimize life-long health and well being considering the inter-generational consequences.